Voltammetric, in-situ spectroelectrochemical and in-situ electrocolorimetric characterization of phthalocyanines - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
In this work, electrochemical, and in-situ spectroelectrochemical characterization of the metallophthalocyanines bearing tetra-(1,1-(dicarbethoxy)-2-(2-methylbenzyl))-ethyl 3,10,17,24-tetra chloro groups were performed. Voltammetric and in-situ spectroelectrochemical measurements show that while cobalt phthalocyanine complex gives both metal-based and ring-based redox processes, zinc and copper phthalocyanines show only ring-based reduction and oxidation processes. The redox processes are generally diffusion-controlled, reversible and one-electron transfer processes. Differently lead phthalocyanine demetallized during second oxidation reaction while it was stable during reduction processes. An in-situ electrocolorimetric method, based on the 1931 CIE (Commission Internationale de I'Eclairage) system of colorimetry, has been applied to investigate the color of the electro-generated anionic and cationic forms of the complexes for the first time in this study. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Cyclic voltammetry; Spectroelectrochemistry; Chromaticity diagram; ELECTROCHEMICAL CHARACTERIZATION; SUBSTITUTED COBALT; ELECTROCATALYTIC ACTIVITY; HYDROGEN-PRODUCTION; METALLOPHTHALOCYANINES; DEMETALATION; ASSIGNMENT; REDUCTION; ZN(II)